Binding conformation and determinants of a single-chain peptide antagonist at the relaxin-3 receptor RXFP3 - Haugaard-Kedström, Linda M. (J Biol Chem, 2018)
The neuropeptide relaxin-3 and its receptor relaxin family peptide receptor-3 (RXFP3) play key roles in modulating behavior such as memory and learning, food intake, and reward seeking. A linear relaxin-3 antagonist (R3 B1-22R) based on a modified and truncated relaxin-3 B-chain was recently developed. R3 B1-22R is unstructured in solution; thus, the binding conformation and determinants of receptor binding are unclear. Here, we have designed, chemically synthesized, and pharmacologically characterized more than 60 analogues of R3 B1-22R to develop an extensive understanding of its structure–activity relationships. We show that the key driver for affinity is the nonnative C-terminal Arg(23). Additional contributors to binding include amino acid residues that are important also for relaxin-3 binding, including Arg(12), Ile(15), and Ile(19). Intriguingly, amino acid residues that are not exposed in native relaxin-3, including Phe(14) and Ala(17), also interact with RXFP3. We show that R3 B1-22R has a propensity to form a helical structure, and modifications that support a helical conformation are functionally well-tolerated, whereas helix breakers such as proline residues disrupt binding. These data suggest that the peptide adopts a helical conformation, like relaxin-3, upon binding to RXFP3, but that its smaller size allows it to penetrate deeper into the orthosteric binding site, creating more extensive contacts with the receptor.